1998
DOI: 10.1097/00001756-199810050-00021
|View full text |Cite
|
Sign up to set email alerts
|

The plantar sole is a ‘dynamometric map’ for human balance control

Abstract: This study investigated the role of the plantar cutaneous information in controlling human balance. We hypothesized that the cutaneous afferent messages from the main supporting zones of the feet have sufficient spatial relevance to inform the CNS about the body position with respect to the vertical reference and consequently to induce adapted regulative postural responses. Skin mechanoreceptors of anterior and/or posterior areas of one or both soles of 10 standing subjects were activated by superficial mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
266
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(298 citation statements)
references
References 9 publications
15
266
0
8
Order By: Relevance
“…The importance of mechanoreceptive information for postural control has been confirmed in several previous investigations (Kavounoudias et al 1998;Stal et al 2003). The destabilizing effects of standing on a foam surface have also been investigated previously in several studies (Blackburn et al 2003;Jeka et al 2004;Vrancken et al 2005).…”
Section: Introductionsupporting
confidence: 56%
“…The importance of mechanoreceptive information for postural control has been confirmed in several previous investigations (Kavounoudias et al 1998;Stal et al 2003). The destabilizing effects of standing on a foam surface have also been investigated previously in several studies (Blackburn et al 2003;Jeka et al 2004;Vrancken et al 2005).…”
Section: Introductionsupporting
confidence: 56%
“…These results supported the hypothesis that the spikes provide relevant tactile information about body position in reference to verticality. As slow adapting receptors code the continuous pressures applied to their field (Kennedy and Inglis 2002), it can be suggested that the spikes are another indented surface that increased the body awareness and improved the spatial representation of the pressure distribution under the feet sole (Wu and Chiang 1997;Kavounoudias et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As the feet interface directly with the ground, cutaneous cues provide very detailed spatial and temporal information about the support surface properties, and about the variations of pressure under the feet that directly result from a shift of the centre of foot pressure (CoP) displacements (Maurer et al 2001;Perry 2006). The plantar sole is a "dynamometric map" (Kavounoudias et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one way of perturbing balance is by altering the information from the somatosensory receptors through vibration of the calf muscles. By vibrating the calf muscles, body sway and torque at the ankles increases (Fransson et al, 2000;Ivanenko et al, 1999;Kavounoudias et al, 1998) and when the vibrations are repeated, the adaptations are evidenced as a decrease in movement variability and ankle torque (Fransson et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%